SOME FINDINGS ON THE POLITICAL PARTICIPATION OF GENERATION Z YOUTH IN TÜRKIYE - Akyol, Ender; Erarslan, Fatih (PEOPLE: International Journal of Social Sciences, 2024)
In recent years, there has been an intense interest in generational studies in many different disciplines of social sciences. Especially the political participation behaviours and voter tendencies of individuals called Generation Z attract the attention of political decision makers as well as academicians. In Türkiye, on the other hand, it is noteworthy that the studies establishing a relationship between the voter tendencies of generations and their political participation preferences and levels are limited and the studies are generally conducted at the regional or educational level on the basis of province, region or school. Based on the assumption that there is a need for a descriptive and explanatory study on the general political participation tendencies of Generation Z in Turkey, this study was designed. In the research, a scale was created to analyse the political participation tendencies of Generation Z youth in Türkiye. Citizens living in Türkiye were considered as the population and the sample to represent the population was determined. Since the variable in question will be measured at the community level, the sample should be distributed at the NUTS II level. Considering the voter turnout rates for a representative sample, the minimum sample size was determined as 417 with a sensitivity of +/- 3 at 95% confidence interval. Considering the possible missing observations, the scale was applied to a total of 500 people. 26 provinces and 31 districts in Level 2 of the "Classification of Statistical Regional Units of Türkiye" were determined as the sample. The data obtained were analysed by using SPSS (Statistical Packages for the Social Sciences) and the general voter tendencies of Generation Z were analysed by reliability analysis, frequency analysis, chi-square analysis and difference tests. In the analyses, it was primarily concluded that 85.8% of the participants were not members of any political party and 67.4% of them did not believe in solving problems through politics. It has been determined that 41.6% of the participants consider themselves as sympathising voters and 34.2% of them consider the party leader important in voting for a political party. In addition, 66.2 per cent of the respondents stated that Turkey needs a new political party and 60.6 per cent stated that Türkiye should return to the parliamentary system.